Microbial Active Matter: A Topological Framework - Sengupta, Anupam (Frontiers in Physics, 2020)
Topology transcends boundaries that conventionally delineate physical, biological, and engineering sciences. Our ability to mathematically describe topology, combined with recent access to precision tracking and manipulation approaches, has triggered a fresh appreciation of topological ramifications in biological systems. Microbial ecosystems, a classic example of living matter, offer a rich test bed for exploring the role of topological defects in shaping community compositions, structure, and functions spanning orders in length and time scales. Microbial activity—characteristic of such structured, out-of-equilibrium systems—triggers emergent processes that endow evolutionary and ecological benefits to microbial communities. The scene stealer of this developing cross-disciplinary field of research is the topological defects: singularities that nucleate due to spontaneous symmetry breaking within the microbial system or within the surrounding material field. The interplay of geometry, order, and topology elicit novel, if not unexpected dynamics that are at the heart of active and emergent processes in such living systems. In this short review, I have put together a summary of the key recent advances that highlight the interface of active liquid crystal physics and the physical ecology of microbes; and combined it with original data from experiments on sessile species as a case to demonstrate how this interface offers a biophysical framework that could help to decode and harness active microbial processes in true ecological settings. Topology and its functional manifestations—a crucial and well-timed topic—offer a rich opportunity for both experimentalists and theoreticians willing to take up an exciting journey across scales and disciplines.